AGGREGATION BEHAVIOR OF POLYETHYLENE GLYCOL IN THE PRESENCE OF ELECTROLYTES AND NON-ELECTROLYTES - Ovais Ali, Noor E Shama, Jamal Ahmad Khan, Elham S. Aazam, S. M. Shakeel Iqubal,Aejaz A. Khan, Tasneem Mohammed,Areej Dawoud, Abdul Rahman Ikbal, KayamkaniAbedulla Khan, M.Z.A. Rafiquee (International Journal of Modern Agriculture, 2020)
Polyethers are the class of organic substances prepared by joining together simpler monomer units by establishing ether links between them. Polyether is also called as Poly(ethylene oxide) or Poly(oxyethylene) based on source and structure respectively. Polyethylene glycole-8000 (PEG), which is highly biocompatible and processable, less toxic and has the greater affinity to couple due to its low molecular weight, as these polyethers are more viscous and colorless. As we know like dissolve like, they are extremely soluble in aqueous and organic solvents. In current work, we measured an exhaustive set of viscosities of Polyethylene Glycol (PEG) having equivalent molecular weight but varying salt concentration in both single as well as double phase section at constant temperature of 28 degree Celsius. As the more and more amount of salt is added, the solution elapsed time is increased and, therefore, the viscosity of solution is also increased. This increment of viscosity is due to the aggregation of PEG as a result of increased salt concentration which occupied the voids in Polyethylene Glycol making it more viscous. The different electrolytic and non-electrolytic salts which we have added in this particular study are sodium chloride (NaCl), sodium dodecyl sulfate (SDS), cetrimonium bromide (CTAB) and starch, glucose gelatin respectively which measures viscosity of PEG by means of Ostwald’s model or Power law model using Ostwald’s viscometer. In the midst of above work we observed that the viscosity of linearly fashioned PEG has been appreciably increased on increasing the concentration of the different salt and vice-versa.